Adult-onset cystic hygroma: A case report of rare entity - Bahl, Sumit (Indian J Dent, 2016)
Cystic hygroma is a benign congenital malformation of the lymphatic system that occurs in infant or children younger than 2 years of age. Although cystic hygroma is well recognized in pediatric practice, it seldom presents de novo in adulthood. These are commonly present in head and neck but can be present anywhere. Cystic hygroma is very rare in adults, but it should be considered in the differential diagnosis of adult neck swellings. Patients presenting with a painless, soft, fluctuant, and enlarging neck mass should have a careful history and physical examination along with radiological imaging to assist with diagnosis. Surgical intervention is the treatment of choice for this rare condition. Here, we are reporting a case of cystic hygroma in a 32-year-old male patient in the neck region. The objectives of this case report are to discuss the clinical presentation, diagnosis, histopathological findings and management of this malformation.